Subclinical LV dysfunction and 10-year outcomes in type 2 diabetes mellitus. Issue 13 (2nd May 2015) - Holland, David J; Marwick, Thomas H; Haluska, Brian A; Leano, Rodel; Hordern, Matthew D; Hare, James L; Fang, Zhi You; Prins, Johannes B; Stanton, Tony
Abstract : Objective: New imaging techniques have permitted the detection of subclinical LV dysfunction (LVD) in up to half of patients with type 2 diabetes mellitus (DM) with a normal EF. However, the connection between early LVD and prognosis is unclear. This study aimed to define the long-term outcome of LVD associated with type 2 DM. Methods: In this prospective cohort study, 230 asymptomatic patients with type 2 DM underwent measurement of global longitudinal 2D strain (GLS) for detection of LVD and were followed for up to 10 years. All subjects had normal EF (≥50%) and no evidence of coronary artery disease at recruitment. Outcome data were obtained through centralised state-wide death and hospital admission registries. The primary endpoint was all-cause mortality and hospitalisation. Results: On study entry, almost half (45%) of the cohort had evidence of LVD as detected by GLS. Over a median follow-up of 7.4±2.6 years (range 0.6–9.7 years), 68 patients (30%) met the primary endpoint (LVD: 37%; normal LV function: 24%). GLS was independently associated with the primary endpoint (HR=1.10; p=0.04), as was systolic blood pressure (HR=1.02; p<0.001) and levels of glycosylated haemoglobin (HR=1.28; p=0.011). Patients with LVD had significantly worse outcome than those without (χ 2 =4.73; p=0.030). Conclusions: Subclinical LVD is common in asymptomatic patients with type 2 DM, is readily detectable by GLS imaging and is independently associated with adverse outcome. Trial registration number: Australian and New Zealand Clinical Trials Registry (ACTRN12612001178831).